Different‐team procurements: A potential solution for the unintended consequences of change in lung allocation policy. Issue 9 (11th March 2021) - Yang, Zhizhou; Gerull, William D.; Shepherd, Hailey M.; Marklin, Gary F.; Takahashi, Tsuyoshi; Meyers, Bryan F.; Kozower, Benjamin D.; Patterson, G. Alexander; Nava, Ruben G.; Hachem, Ramsey R.; Witt, Chad A.; Byers, Derek E.; et al.
Abstract : The new lung allocation policy has led to an increase in distant donors and consequently enhanced logistical burden of procuring organs. Though early single‐center studies noted similar outcomes between same‐team transplantation (ST, procuring team from transplanting center) and different‐team transplantation (DT, procuring team from different center), the efficacy of DT in the contemporary era remains unclear. In this study, we evaluated the trend of DT, rate of transplanting both donor lungs, 1‐year graft survival, and risk of Grade 3 primary graft dysfunction (PGD) using the Scientific Registry of Transplant Recipient (SRTR) database from 2006 to 2018. A total of 21619 patients (DT 2085, 9.7%) with 19837 donors were included. Utilization of DT decreased from 15.9% in 2006 to 8.5% in 2018. Proportions of two‐lung donors were similar between the groups, and DT had similar 1‐year graft survival as ST for both double (DT, HR 1.108, 95% CI 0.894–1.374) and single lung transplants (DT, HR 1.094, 95% CI 0.931–1.286). Risk of Grade 3 PGD was also similar between ST and DT. Given our results, expanding DT may be a feasible option for improving lung procurement efficiency in the current era, particularly in light of the COVID‐19 pandemic. Abstract : Risk‐adjusted analyses for both single and double lung transplants shows that transplantation of lungs procured by a team different than the transplant team versus the transplant team has similar 1‐year graft survival and risk of grade 3 primary graft dysfunction.